Designing a Structural Model of Marital Satisfaction Based on the Components of Systemic–Spiritual Couple Therapy with the Mediating Role of Power Structure in the Family - Yavari, Sepideh; Janbozorgi, Masoud; Houshyari, Jafar (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to design and validate a structural model of marital satisfaction based on the components of systemic–spiritual couple therapy, with the mediating role of the family power structure. Methods and Materials: The research adopted a descriptive–correlational design with an applied objective. The statistical population included all couples in Isfahan who had been married for at least five years. Using convenience sampling, 384 participants (192 couples) were selected from counseling centers. Participants completed the ENRICH Marital Satisfaction Questionnaire, the Family Power Structure Questionnaire, and the Systemic–Spiritual Couple Therapy Scale. Data were analyzed using Pearson correlation, multiple regression, and structural equation modeling (SEM) with AMOS software. Findings: Results showed that systemic–spiritual couple therapy had a significant positive effect on marital satisfaction (β = 0.54, p < 0.001) and on the family power structure (β = 0.61, p < 0.001). The family power structure also significantly predicted marital satisfaction (β = 0.24, p < 0.01), confirming its mediating role. The overall model demonstrated good fit indices, supporting the hypothesized relationships among variables. Regression analysis also revealed that the components of systemic–spiritual couple therapy and family power structure together explained 25% of the variance in marital satisfaction (R² = 0.25, F = 66.51, p < 0.001). Conclusion: The findings support the effectiveness of systemic–spiritual couple therapy in enhancing marital satisfaction, both directly and indirectly through improvements in family power dynamics. The proposed model underscores the importance of integrating spiritual and systemic interventions with structural family variables to improve relationship outcomes.